Comparison of quick sequential organ failure assessment and modified systemic inflammatory response syndrome criteria in a lower middle income setting - Beane, A; De Silva, AP; Munasinghe, S; De Silva, N; Arachchige, SJ; Athapattu, P; Sigera, PC; Miskin, MF; Liyanagama, PM; Rathnayake, RMD; Jayasinghe, KSA; Dondorp, AM; et al. (Airiti Press Inc, 2017)
Introduction: Quick Sequential Organ Failure Assessment (qSOFA) is potentially feasible tool to identify risk of deteriorating in the context of infection for to use in resource limited settings. Purpose: To compare the discriminative ability of qSOFA and a simplified systemic inflammatory response syndrome (SIRS) score to detect deterioration in patients admitted with infection. Methods: Observational study conducted at District General Hospital Monaragala, Sri Lanka, utilising bedside available observations extracted from healthcare records. Discrimination was evaluated using area under the receiver operating curve (AUROC). 15,577 consecutive adult ( ≥ 18 years) admissions were considered. Patients classified as having infection per ICD-10 diagnostic coding were included. Results: Both scores were evaluated for their ability to discriminate patients at risk of death or a composite adverse outcome (death, cardiac arrest, intensive care unit [ICU], admission or critical care transfer). 1844 admissions (11.8%) were due to infections with 20 deaths (1.1%), 29 ICU admissions (1.6%), 30 cardiac arrests and 9 clinical transfers to a tertiary hospital (0.5%). Sixty-seven (3.6%) patients experienced at least one event. Complete datasets were available for qSOFA in 1238 (67.14%) and for simplified SIRS (mSIRS) in 1628 (88.29%) admissions. Mean (SD) qSOFA score and mSIRS score at admission were 0.58 (0.69) and 0.66 (0.79) respectively. Both demonstrated poor discrimination for predicting adverse outcome AUROC = 0.625; 95% CI, 0.56-0.69 and AUROC = 0.615; 95% CI, 0.55- 0.69 respectively) with no significant difference (p value = 0.74). Similarly, both systems had poor discrimination for predicting deaths (AUROC = 0.685; 95% CI, 0.55-0.82 and AUROC = 0.629; 95% CI, 0.50-0.76 respectively) with no statistically significant difference (p value = 0.31). Conclusions: qSOFA at admission had poor discrimination and was not superior to the bedside observations featured in SIRS. Availability of observations, especially for mentation, is poor in these settings and requires strategies to improve reporting.